CT evaluation of living liver donor: Can 100-kVp plus iterative reconstruction protocol provide accurate liver volume and vascular anatomy for liver transplantation with reduced radiation and contrast dose?. Issue 23 (June 2017) - Yoshida, Morikatsu; Utsunomiya, Daisuke; Kidoh, Masafumi; Yuki, Hideaki; Oda, Seitaro; Shiraishi, Shinya; Yamamoto, Hidekazu; Inomata, Yukihiro; Yamashita, Yasuyuki
Abstract : Abstract: We evaluated whether donor computed tomography (CT) with a combined technique of lower tube voltage and iterative reconstruction (IR) can provide sufficient preoperative information for liver transplantation. We retrospectively reviewed CT of 113 liver donor candidates. Dynamic contrast-enhanced CT of the liver was performed on the following protocol: protocol A (n = 70), 120-kVp with filtered back projection (FBP); protocol B (n = 43), 100-kVp with IR. To equalize the background covariates, one-to-one propensity-matched analysis was used. We visually compared the score of the hepatic artery (A-score), portal vein (P-score), and hepatic vein (V-score) of the 2 protocols and quantitatively correlated the graft volume obtained by CT volumetry (graft-CTv) under the 2 protocols with the actual graft weight. In total, 39 protocol-A and protocol-B candidates showed comparable preoperative clinical characteristics with propensity matching. For protocols A and B, the A-score was 3.87 ± 0.73 and 4.51 ± 0.56 ( P < .01), the P-score was 4.92 ± 0.27 and 5.0 ± 0.0 ( P = .07), and the V-score was 4.23 ± 0.78 and 4.82 ± 0.39 ( P < .01), respectively. Correlations between the actual graft weight and graft-CTv of protocols A and B were 0.97 and 0.96, respectively. Liver-donor CT imaging under 100-kVp plus IR protocol provides better visualization for vascular structures than that under 120-kVp plus FBP protocol with comparable accuracy for graft-CTv, while lowering radiation exposure by more than 40% and reducing contrast-medium dose by 20%.